2011
DOI: 10.1002/cmdc.201100014
|View full text |Cite
|
Sign up to set email alerts
|

Oxidatively Activated DNA‐Modifying Agents for Selective Cytotoxicity

Abstract: DNA-modifying agents are stalwarts of chemotherapeutic cancer treatments, but require significant design improvements to improve selectivity, minimize side effects, and for their widespread use to continue. Herein we present a novel design strategy in which DNA-modifying agents contain an oxidizable leaving group and a nitrogen mustard. The agents form strong electrophiles specifically when oxidized. Activation, measured by hydrolysis, illustrates that oxidants increase reactivity 1700-fold. Reaction in the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 31 publications
0
23
0
Order By: Relevance
“…On the other hand, recently studies showed that the cytotoxicity of alkylating reagents can be enhanced by ROS, by formation of ROS-activated prodrugs resulting in higher DNA crosslink activity. Peng's group revealed that the prodrugs of nitrogen mustard coupled with an ROS trigger unit can be triggered by H 2 O 2 to release active anticancer drugs with higher DNA crosslink activities, leading to selective toxicity toward primary leukemic lymphocytes but less toxic to normal lymphocytes [32], [33], [34], [35], [36]. In this study, we found that ROS induced by SC-514 enhanced nitrosoureas-induced DNA crosslink and cytotoxicity (Fig.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…On the other hand, recently studies showed that the cytotoxicity of alkylating reagents can be enhanced by ROS, by formation of ROS-activated prodrugs resulting in higher DNA crosslink activity. Peng's group revealed that the prodrugs of nitrogen mustard coupled with an ROS trigger unit can be triggered by H 2 O 2 to release active anticancer drugs with higher DNA crosslink activities, leading to selective toxicity toward primary leukemic lymphocytes but less toxic to normal lymphocytes [32], [33], [34], [35], [36]. In this study, we found that ROS induced by SC-514 enhanced nitrosoureas-induced DNA crosslink and cytotoxicity (Fig.…”
Section: Discussionmentioning
confidence: 54%
“…Recently studies demonstrated that the cytotoxicity of alkylating reagents can be enhanced by ROS with the effects of enhanced DNA crosslink levels and deleterious DNA damages (e.g., ICL formation or alkylation) [32], [33], [34], [35], [36]. Therefore, we further tested whether ROS would alter the DNA crosslink induced by nitrosoureas.…”
Section: Resultsmentioning
confidence: 98%
“…For example, cisplatin has been shown to form cross-links with nucleic acids to halt DNA replication and transcription [1, 2]. A major problem with these agents are so called “off-target” effects wherein non-cancer cells are effected by these DNA modification reactions [3, 4]. This problem generally leads to drug induced toxicity, side effects, and little margin for error between the therapeutic dose and the toxic dose.…”
Section: Introductionmentioning
confidence: 99%
“…As a starting point, compounds 1b – e were examined for activity in MCF-7 breast cancer cells using letrozole as a positive control. 18 To examine activity, MCF-7 cells were grown under two different conditions. First, as is standard MCF-7 cells were raised in estrogen, low picomole, which has been shown to increase both estrogen and estrogen receptor content.…”
Section: Resultsmentioning
confidence: 99%